A review Review on Co-Crystals New Approach to Modify the Physicochemical Characteristics of API - Joshi, Varda; Raut, Poonam; Bhosale, Nikita (Asian Journal of Pharmaceutical Research and Development, 2023)
The expansion of a novel product is constrained by an active medicinal ingredient's poor solubility in aqueous solutions and limited oral bioavailability. A novel strategy to improve the physicochemical characteristics of the active medicinal ingredient is co-crystal formation. The pharmacological action of the API is unaffected by co-crystallization with pharmaceutically acceptable molecules, although it can enhance the physical characteristics like solubility, stability, and dissolution rate. Cocrystals are multi-component systems comprising active medicinal ingredients that also contain a stoichiometric amount of a coformer that is acceptable to the pharmaceutical industry. The pharmaceutical business has a significant chance to create new medicinal products since producing pharmaceutical co-crystals can enhance a drug's physicochemical qualities.The most major benefit of co-crystals is their ability to produce novel medications with improved solubility, which increases the effectiveness and safety of the treatment. The thermodynamic stability of the co-crystal preparation is the key influencing factor. Co-crystal screening provides information on the chemical composition and connection between the active medicinal ingredient and the coformer. This review discusses the many co-crystal synthesis techniques, including hot-melt extrusion, slurrying, antisolvent, grinding, and spray drying. Here is a quick explanation of the characteriszation methods frequently employed for co-crystals, as well as their uses in medicine. Here are some quick summaries of reported research on co-crystals that were evaluated in order to better grasp the notion of co-crystals.